Renewable Energy Access Challenge at Household Level for the Poor in Rural Zimbabwe: Is Biogas Energy a Remedy? - Maramura, Tafadzwa Clementine; Maziriri, Eugine Tafadzwa; Chuchu, Tinashe; Mago, David; Mazivisa, Rumbidzai (International Journal of Energy Economics and Policy, 2020)
This study examined Zimbabwe's energy access situation and suggests that Zimbabwe's energy access solution goes beyond providing biogas energy alone but needs addressing the root causes of Zimbabwe's inability to access renewable energy. The paper also challenges biogas fuel prospects and shortcomings. A mixed-method methodology has been used. Next, the qualitative data analysis was carried out using thematic analysis. The themes emerging from the findings include lack of knowledge about biogas power, difficulties in accessing start-up capital, and lack of resources needed. From a quantitative viewpoint, it was discovered that lack of adequate funds, high installation costs, lack of adequate data and negative attitudes to the community are some of the challenges that block biogas to be considered as renewable energy for the poor in rural Domboshava, Zimbabwe at household level. Based on the findings of the article, organizational consequences are explored, and recommendations are made for shortcomings and future directions for analysis. Broadly speaking, this study adds enormously new knowledge to the existing energy economics literature in Africa— a context that some scholars in developing countries still ignore most. Keywords: waste management, energy poverty, firewood, deforestation, sustainable development JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.8801